Participatory Governance The Missing Link for Poverty Reduction - Schneider, Hartmut (OECD Development Centre Policy Briefs, 1999)
• Empowerment of the poor is one ingredient in effective poverty reduction. • A demand-driven participatory approach enhances effectiveness and efficiency. • Accountability is the central lever for participatory governance. • Capacity building is necessary for making participatory governance a reality